Empirical analysis and optimization suggestions of Peking Opera audience's use intention of Kuaishou app - Shixia, Yang; Alexander, Chelum (Arts and Science Press Pte. Ltd, 2026)
To verify the validity of the integrated "UTAUT2-SOR" model constructed in the previous study and reveal the influencing mechanisms of Peking Opera audiences' intention to use Kuaishou APP, this paper adopted the questionnaire survey method (N=516) and Structural Equation Modeling (SEM) to systematically test the functional relationships among external stimulus factors, mediating variables and moderating variables. The results show that effort expectancy, social influence, platform characteristics, cultural identity and social interaction all exert a significant direct effect on Peking Opera audiences' intention to use Kuaishou APP, and meanwhile, usage attitude and user satisfaction also demonstrate a direct driving effect on such intention. The analysis of the mediating mechanism indicates that usage attitude has a significant mediating effect in the paths where effort expectancy and facilitating conditions influence usage intention, while satisfaction shows an obvious mediating effect in the paths where platform characteristics and cultural identity affect usage intention. The test of the moderating effect finds that Peking Opera exposure experience produces a significant moderating effect in all paths where independent variables influence usage intention, while age only exerts a specific moderating effect in the paths of effort expectancy and algorithm recommendation on usage intention. In addition, users' usage habits show an important moderating effect in the paths of 8 types of independent variables (such as performance expectancy and platform characteristics) on usage intention, whereas gender has no significant moderating effect in all paths. Based on the above conclusions, 12 practical suggestions are put forward from four dimensions, namely "optimization of operational convenience", "innovation of platform functions", "deepening of cultural identity" and "differentiated operation", with detailed specific implementation measures provided. This study offers empirical support and operable guidance for Kuaishou to improve the communication effect of Peking Opera content and enhance user stickiness.